A carotenoid cleavage dioxygenase 4 from Paulownia tomentosa determines visual and aroma signals in flowers. (April 2023) - Morote, Lucía; Rubio-Moraga, Ángela; López-Jiménez, Alberto José; Argandoña, Javier; Niza, Enrique; Ahrazem, Oussama; Gómez-Gómez, Lourdes
Abstract: Paulownia tomentosa is an economically important fast-growing tree, and its flowers and fruits are a rich source of biologically active secondary metabolites. In addition, the flowers of P. tomentosa are distinguished by a strong aroma and are also excellent nectariferous plants. The flowers are pale lilac and characterized by the presence of yellow nectar guides, whose color changes during the development of the flower, representing reliable signals to pollinators while enhancing reproductive success. The chemical analyses of the nectar guides revealed the presence of carotenoids as the pigments responsible for the observed coloration, with β-carotene levels determining the color changes observed after anthesis, with a reduction at anthesis and further increase and accumulation in post anthesis. To understand how β-carotene accumulation was controlled in the nectar guides, the expression of genes related to carotenoid biosynthesis and metabolism was analyzed. Carotenogenic gene expression was not associated with the observed changes in β-carotene during flower development. However, the expression of a gene encoding a carotenoid cleavage dioxygenase, CCD4–4, was co-related with the levels of β-carotene in the nectar guides. In addition, CCD4–4 cleavage β-carotene at C9-C10 and C9'-C10' positions, resulting in the generation of β-ionone, which was detected in flowers at anthesis. The obtained results indicated a developmental stage specific regulation of apocarotenoid formation through β-carotene cleavage, resulting in color changes and volatile production as key traits for plant-pollinator interactions. Data availability: Data will be made available on request. Highlights: The CCD4 family in P. tomentosa is a multigene family. β-carotene levels are highly increased in post-anthesis flowers. β-ionone is emitted in flowers at anthesis. CCD4-4 is responsible of β-carotene degradation of nectar guides.